Design of a Green SCOR-Based Performance Assessment Model for an Organic Skincare Supply Chain - Yelita Anggiane Iskandar; Resista Vikaliana; Zetira Barges (Universitas Serang Raya, 2026)
This study aims to evaluate the supply chain performance at PT Nectars Natura Karya, an organic skincare manufacturer, using the Green Supply Chain Operations Reference (SCOR) model approach combined with the Analytic Hierarchy Process (AHP) method for determining the weight of key performance indicators (KPI). A total of 15 KPIs were used in the measurement, covering general operational aspects and environmental sustainability. The evaluation was conducted by calculating the actual value, normalization, and combining the AHP weights to obtain the final score of each indicator. The measurement results show that the final value of the company's supply chain performance is 42.59 from a maximum score of 77.77, with an actual achievement rate of approximately 54.76%. Based on the classification of the Snorm de Boer method, this value is included in the category of average performance, which shows that the company has sufficient performance; however, there is still room for improvement. The largest contribution came from general operational KPIs (91.69 %), while KPIs classified as green supply chains only accounted for 8.36% of the total score. The results of the assessment using the traffic light system (TLS) method show that there are seven KPIs that are still in the red category and need immediate improvement, and four KPIs are in the yellow category that are close to the target but still need periodic monitoring. The managerial implications of these results emphasize the importance of strengthening environmental aspects in the supply chain, including waste measurement, improved employee training, and compliance with sustainability standards by suppliers.